ANALYSIS OF METHODS AND MEANS OF DETERMINING THE ACTUAL TECHNICAL CONDITION OF OIL AND GAS PIPELINES AND CALCULATING THE RESIDUAL RESOURCE - Martyniuk, R. Т. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
The main principle of diagnosing metal structures of long-term operation, and pipelines in particular, is based on consistent and systematic measurements of certain parameters of the structure, on detecting changes in these parameters during operation and comparing them with the original ones, and on forecasting changes in these parameters. In order to make informed decisions regarding the term of further operation of the pipeline, the order and scope of repair works, the establishment of suitable terms for the nearest diagnostic examinations or operational monitoring of parameters that are critical, an assessment of the actual technical condition of the pipeline is carried out, and based on its results, the calculation of the residual resource. The calculation of the residual resource consists in checking the fulfillment of the condition of the transition of the structure (with or without a defect) to the critical state under the maximum operating parameters of loads and taking into account the rate of growth of defects over time (changes in the size of the defect), changes in the mechanical characteristics of the material. The calculation of the residual resource consists in checking the fulfillment of the condition of the transition of the structure (with or without a defect) to the critical state under the maximum operating parameters of loads and taking into account the rate of growth of defects over time (changes in the size of the defect), changes in the mechanical characteristics of the material. The estimated residual resource is determined by the minimum time interval from the current state to the final state, which corresponds to the destruction of the structure. Physical parameters are divided into the following groups: kinematic, geometric, static, dynamic, thermal, acoustic, electric and magnetic, mechanical, atomic-physical, as well as those based on the molecular properties of materials. The measurement of physical parameters is the basis of various methods and means of technical diagnostics, which are used to analyze the state of the structure. The most important in the practice of technical diagnostics are the parameters of the reliability and survivability of the metal structure, which are functionally dependent on the measured values obtained by conducting electrometry, vibroacoustics, defectoscopy, structuroscopy, measurement of mechanical properties, substance composition, and deformations.